CONSUMPTION BEHAVIOR OF FARMER HOUSEHOLDS IN RURAL SUMBAWA, INDONESIA - Achmad, Budiman; Diniyati, Dian (Association of Indonesian Forestry and Environment Researchers and Technicians, 2018)
The welfare level of farmer in rural Sumbawa was steadily low although the potency of natural resources at their vicinity was high. This paper determines the consumption behaviour as well as the welfare level a farmer households in rural Sumbawa, Indonesia. The household size, years of education, and farming incomes were used as indicators of on-farm performance. This research was carried out in February until April 2015 at two separate forest areas which were administratively under Labuhan Badas village, i.e. community forestry (HKm) in the state production forest and private owned forests (POF). A number of 34 respondents perlocation were purposively selected. The multiple linear regression was implemented to analyze factors affecting farmer household consumption behaviour, while the exchange value for income earned by farmer (EVIF) was incorporated to measure the welfare level. The regression revealed that the consumption behaviour at two groups of respondents were positively related with three indicators, i.e. household size, years of education, and farming incomes. Meanwhile, the household size affected the consumption behaviour of the HKm farmers but not the POF farmers. Furthermore, the consumption is strongly affected by the income generated from both forest areas. The EVIF approach revealed that the welfare of whole farmers were still low (EVIF = 0.74-0.99).